সংবাদপত্রের সম্পাদকীয় নীতিমালা - রহমান, রাফিজা (এম এম সি সেমিনার সংকলন ;)
Contributed articles on social perspectives of mass media and adequacy of press coverage in Bangladesh; edited papers of various seminars.